Audit of facilities management performance in higher education properties. Case studies: Universiti Teknologi Mara (UiTM) and Universiti Malaya (UM) / Hasnan Hashim, Mohd Esham Mamat and Noorazlina Kamarulzaman - Hashim, Hasnan; Mamat, Mohd Esham; Kamarulzaman, Noorazlina (Research Management Institute (RMI), 2011)
Performance management has a strong relationship with facilities management practices. The unclear information of the method of managing performance in higher education properties is emerged the research to be undertaken. In order to identify the relationship and the implementation of FM performance in higher education properties in Malaysia, this dissertation has been carried out. The first objective of doing this research is to identify the method FM performance management in higher education properties of public university. The second objective is to identify problem associated with the FM implementation within the higher education organizations. Analysis for the research comprises of comparative and descriptive approach as well as qualitative and quantitative analysis which are based on case studies, interview and structured questionnaire. The findings revealed that performance management practices is systematically established, implemented and enforced as part of their quality objectives achievements by introduced the performance indicators and using the four tested research variables which are flexibility, effectiveness, efficiency and creativity. The opinions gathered from respondents are very encouraging. The information is obtained from FM personnel in multiple disciplines and customer (students, ordinary staff and public) where the results are thoroughly analyzed. At the end of this paper is proposed a basic framework of FM performance in higher education properties highlighted the areas that type of assessment that should be done. From the findings, the author anticipate that this research would provide better understanding and perception to the readers on the FM performance management in higher education properties and the extent of its benefits as well.